2020
DOI: 10.2147/ijn.s269880
|View full text |Cite|
|
Sign up to set email alerts
|

<p>Green Synthesis of Silver Nanoparticles Using Extract of <em>Jasminum officinal</em> L. Leaves and Evaluation of Cytotoxic Activity Towards Bladder (5637) and Breast Cancer (MCF-7) Cell Lines</p>

Abstract: Introduction: Jasminum officinale L. is a very important medicinal and industrial flowering aromatic plant. Methods: The present study deals with Jasminum officinale L. leaves extract (JOLE) as a reducing and capping agent for the synthesis of silver nanoparticles (AgNPs) by the green pathway. Phenolic profile of the extract was evaluated using HPLC-PDA/MS/MS technique. Jasminum officinale L. leaves extract silver nanoparticles (JOLE-AgNPs) were characterized by ultraviolet light (UV), Fourier transform infrar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…10 Because of their unique chemical properties, NPs fabricated by a flowermediated procedure are more efficient than those synthesized using other biological materials. 11,12 The flowers of many plants contain diverse secondary compounds that function as reducing and stabilizing agents and as precursor molecules involved in the formation of NPs. 13 Numerous studies have reported the production or synthesis of AgNPs by microwave-assisted, phase transfer, electrochemical, and photochemical methods, but these synthesis steps require toxic chemicals.…”
Section: Introductionmentioning
confidence: 99%
“…10 Because of their unique chemical properties, NPs fabricated by a flowermediated procedure are more efficient than those synthesized using other biological materials. 11,12 The flowers of many plants contain diverse secondary compounds that function as reducing and stabilizing agents and as precursor molecules involved in the formation of NPs. 13 Numerous studies have reported the production or synthesis of AgNPs by microwave-assisted, phase transfer, electrochemical, and photochemical methods, but these synthesis steps require toxic chemicals.…”
Section: Introductionmentioning
confidence: 99%
“…The surface charge of biogenic AgNPs has been observed to be −10.8 mV ( Figure 3D ). ζ-potential measures AgNPs stability by investigating the surface charge potential in aqueous suspensions ( Elhawary et al, 2020 ). A negative charge on the surface of biogenic AgNPs indicates high stability of AgNPs ( Römer et al, 2011 ).…”
Section: Resultsmentioning
confidence: 99%
“…It is based on the ability of viable cells to incorporate and bind the supravital dye neutral red in lysosomes [ 112 ]. Neutral red uptake has been employed to evaluate the toxicity induced by AgNPs synthesized by a green route in bladder (5637) and breast (MCF-7) cancer cell lines [ 113 ]. One more common method to determine cytotoxicity measures the activity of cytoplasmic enzymes released by damaged cells.…”
Section: Cancer Evaluation Modelsmentioning
confidence: 99%